2008
DOI: 10.1080/00207450701239459
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study of Simulator Sickness: Differences in EEG Response Due to Individual Sensitivity

Abstract: This study identifies differences in the electroencephalogram (EEG) responses caused by individual sensitivity to simulator sickness. Simulator sickness was investigated by studying the changes in simulator sickness in two different subject groups (sick group and nonsick group). Subjective evaluations using the simulator sickness questionnaire and the EEG response data were gathered every 5 min while the subjects were driving at 60 km/h for 60 min in the driving graphic simulator. The response to every item of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 7 publications
1
23
1
5
Order By: Relevance
“…This finding is consistent with that of other studies (Domeyer et al, 2013;Howarth & Hodder, 2008;Kennedy et al, 2000;Park et al, 2008;Stanney et al, 2003). However, symptom intensity in the third session was significantly higher than that in the second session.…”
Section: Adaptation To Driving Simulatorsupporting
confidence: 83%
See 1 more Smart Citation
“…This finding is consistent with that of other studies (Domeyer et al, 2013;Howarth & Hodder, 2008;Kennedy et al, 2000;Park et al, 2008;Stanney et al, 2003). However, symptom intensity in the third session was significantly higher than that in the second session.…”
Section: Adaptation To Driving Simulatorsupporting
confidence: 83%
“…In most individuals experiencing simulator sickness, symptoms increase over the course of a single session but decrease from one session to another (Domeyer, Cassavaugh, & Backs, 2013;Howarth & Hodder, 2008;Kennedy, Stanney, & Dunlap, 2000;Park et al, 2008;Stanney et al, 2003). Although the majority of trainees adapt to driving simulators, it appears that approximately 3% of the population is incapable of adapting to virtual environments (Howarth & Hodder, 2008).…”
Section: Adaptation To Virtual Realitymentioning
confidence: 99%
“…First, the decrease of mean values of PLI and NMI in the unrecognized SD condition indicated a weaker functional connectivity level in the theta band. EEG alpha and theta waves are thought to reflect a person's cognitive and memory ability [22], and as visually evoked SD can provoke motion sickness, most studies found that theta band was an effective parameter to measure visually induced motion sickness, such as that Byung, et al [13] found that there was the highest correlation between parameter of theta and subjective report of visual SD and motion sickness, similarly, in the study of Park, et al [23], theta band was considered an effective physiological parameter for evaluating visually induced motion sickness and they also found different subject groups (sick and nonstick of motion sickness) were statistically different with respect…”
Section: Discussionmentioning
confidence: 71%
“…It is generally accepted that an intact vestibular system is required in order for motion sickness to be experienced Bouyer and Watt 1996). Reason and Brand (1975) report that between 1945 and 1960, the dominant theory was that motion sickness was caused by an excessive stimulation of the vestibular system (vestibular "overstimulation" theory). However, the observation of visually induced motion sickness (e.g.…”
Section: Sensory Conflict Theorymentioning
confidence: 98%
“…The theory most often used to explain the occurrence of sickness is sensory conflict theory (Reason and Brand 1975). The following section provides a brief outline of this theory, summarises its application to VR and considers other theories that have been proposed to explain the experience of sickness when using a VE.…”
Section: 1 Introductionmentioning
confidence: 99%